Pengaruh Model Pembelajaran CLIS (Children Learning In Science) terhadap Peningkatan Literasi Sains Siswa SD Negeri 2 Banaran Kertosono - Wahyu Lailatul Baridah (-)
Science learning must oversee the daily life of students. Students are given the opportunity to ask questions, generate ideas, build curiosity about everything in their environment, build the necessary skills, and raise students' awareness that learning science is indispensable for learning. The purpose of this study was to describe and explain the effect of the CLIS (Children Learning In Science) learning model on improving elementary students' scientific literacy. The approach used in this research is a quantitative approach with the type of quasi-experimental research and data analysis techniques using the statistical model Independent Samples T Test. The results of this study indicate that there is a significant effect of the CLIS (Children Learning In Science) learning model on the increase in scientific literacy of fifth grade students of SD Negeri 2 Banaran Kertosono. In other words, the CLIS (Children Learning In Science) learning model affects elementary students' scientific literacy.